A study of the influence of spacing within rows and seed tuber size upon the yield of the potato crop : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agriculture Science at Massey University, New Zealand - Anang, Husin (Massey University, 1966)
Undoubtedly there is a need for more intensive research on improving methods of growing potatoes. One aspect which has a major influence on plant population is seed spacing and seed size. The project reported herein was designed to study the effect of different levels of spacing and seed size, together with their interactions, on terminal yield of potato crops. In view of the need to study other important factors influencing yield, the investigation was extended to include the effects of seed spacing and size on growth and development of the crops.
Keywords: Potatoes; Spacing; Yields; 300802 Horticultural crop growth and development